2011
DOI: 10.1190/1.3587222
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the airwave in time-domain marine controlled-source electromagnetics

Abstract: In marine time-domain controlled-source electromagnetics (CSEM), there are two different acquisition methods: with horizontal sources for fast and simple data acquisition or with vertical sources for minimizing the effects of the airwave. Illustrations of the electric field as a function of space and time for various source antenna orientations, based on analytical formulation of the electric field in two half-spaces, provide insights into the properties of the airwave and the nature of diffuse electric fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Hunziker et al (2011) showed for a marine environment that for a slightly dipping vertical source, the air-wave contribution to the full electric field is significant. Because E z commonly is more than an order of magnitude smaller than the horizontal electric field, not knowing the borehole tilt and thus not accounting for it, would result in wrong interpretation.…”
Section: Sensitivity Of the Near-surface Ez In Land Csem Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Hunziker et al (2011) showed for a marine environment that for a slightly dipping vertical source, the air-wave contribution to the full electric field is significant. Because E z commonly is more than an order of magnitude smaller than the horizontal electric field, not knowing the borehole tilt and thus not accounting for it, would result in wrong interpretation.…”
Section: Sensitivity Of the Near-surface Ez In Land Csem Monitoringmentioning
confidence: 99%
“…The drawback of lower amplitudes of E z should be compensated by the fact that the 'air-wave', which masks much of the subsurface response, is polarized horizontally and thus has no strength in the vertical electric field (Hunziker et al, 2011;Singer and Atramonova, 2013). Furthermore, noise levels should be lower in E z than in the horizontal field components, because the receivers are planted in boreholes, slightly further from most electric infrastructure than horizontal dipole receivers.…”
Section: Measurement Of E Z On Landmentioning
confidence: 99%
“…The use of vertical sources and/or receivers has also been proposed by Holten et al (2009) the vertical component of the electric field has no TE component and hence no airwave component. Hunziker et al (2011) showed that a deviation from the vertical of 0.05°can result in an airwave contribution of 20% of the total field. Amundsen et al (2006) describe a technique for airwave removal based on wavefield separation into upgoing and downgoing fields.…”
Section: Airwave Mitigation Techniquesmentioning
confidence: 98%
“…The receivers can be deployed on the seafloor [60] or towed behind the source [28,61]. For shallow waters where the gas hydrate is usually buried, the airwave dominates the recorded EM signals and it will mask the useful signals from the seafloor hydrate target [62][63][64][65][66]. The airwave is mainly the signals from the source which propagates upward to the sea surface, travels through the air horizontally and finally goes down into the water column to the receivers [67].…”
Section: Introductionmentioning
confidence: 99%